Comparison of Linear Elamite and Indus Writing Systems - Andreas Fuls (Iranian Journal of Archaeological Studies)
Linear Elamite writing was used during the Bronze Age in the southwestern lowlands and central highlandsof the Iranian plateau. The comparison of Linear-Elamite and Indus writing from the northern part of the Indiansubcontinent contribute to our understanding of literacy in these regions. They are, as far as we can tell, notdirectly related to each other, but the idea of writing and the general way of creating pictographic and abstractgraphemes representing a language and transmitting meaning may have spread from one region to the other sincethe beginning of the Middle Bronze age around 2200 BCE. Both writing systems share several features such asgeneral methods of sign modification and reading direction, but the type of writing and degree of phonetizationseems to be very different. Therefore, the exploration and comparison of both writing systems will contribute tothe overall study of the origin of writing in Southwest Asia.